Training in finance and business plan for entrepreneurs in the IUHIBA Biomedical Engineering program - Dumas, Mónica E.; Ríos, Mariana B.; Perdiz, Natalia P.; Risk, Marcelo R. (Revista del Hospital Italiano de Buenos Aires, 2022)
This paper raises the importance of including financial education and business plan in the training process of biomedical engineering professionals so that, as entrepreneurial professionals and according to the needs of society, they adequately perform their key role in innovation and development of new technologies.
Keywords: training; Biomedical Engineering; IUHIBA